(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Incursion finding is a process of identifying and responding malicious activity. Wireless sensor webs consisting bulk of ‘sensors’ are useful to integrate data in variety of environment. The basic sensors are simple and have limited power supplies. Heterogeneous wireless sensor webs are better scalable and lower overall cost than homogeneous sensor webs. In this paper, we are improving the lifetime of wireless web and we present a survey of various energy efficient techniques in a various wireless sensor web. It is important to improving wireless web because sensor nodes in wireless webs are constrained by limited energy.